Effects of Ginger (Zingiber officinale) and Garlic (Allium sativum) Supplemented Diets on Growth and Feed Utilization of Rainbow Trout (Oncorhynchus mykiss) Juvenile - Mahato, Ishori Singh; Paudel, Krishna; Gurung, Gun Bahadur (Nepalese Journal of Aquaculture and Fisheries, 2023)
Incorporation of herbal additives into fish diets has emerged as a promising strategy to boost growth and bolster immunity in aquaculture. This study aimed to evaluate the impact of two such additives, ginger (Zingiber officinale) and garlic (Allium sativum), on the growth and feed efficiency of rainbow trout (Oncorhynchus mykiss). For this, 3600 trout averaging 3.52 ± 0.15 g, allocated to 15 raceway tanks, housing 240 fish per tank were fed diets containing varying levels of ginger (1 and 2%) and garlic (1 and 2%), alongside a control group with no additives over a 60-days period at 5% of their body weight. Results revealed that the final weight (22.0±0.8g), weight gain (18.3±0.8g), specific growth rate (SGR) (2.97±0.04%/day) and condition factor (2.39±0.36) were significantly higher (p< 0.05) in 1% ginger-supplemented groups compared to the control and garlic-supplemented groups. Similarly, fish fed with 2% ginger exhibited significantly higher SGR than control and 1% garlic fed groups. However, there was no significant difference between 2% ginger, 1 and 2% garlic, and control group in terms of weight gain. The survival rates remained consistent across the treatments. Consequently, this study advocates for the inclusion of 1% ginger in rainbow trout diets as a viable, cost-efficient, and eco-friendly means of enhancing growth.